Features of structure of skin of hairy part of head of men at androgenic defluxion - Kostilenko Yu.P.; Tikhonova O.A. (Морфологія, 2009)
Utilized by us universal innovative method of morphological researches provided the receipt of original information, which not only complement the known facts but also in more depth expose principles of device of skin of hairy part of head of men in a norm and after an androgenic pelade. In the process of androgenic pelade degradation foremost intradermal hair follicles undergo sclerosis. In the reticulated layer of derma degrading hair follicles substituted with connective tissue. Complete loss of hair at an androgenic defluxion, results in compensatory reorganization of skin of hairy part of head, which is expressed in a substitution of hypodermis connecting tissue by fatty tissue, blood vessels formation in all layers of skin of with prevaliation of venous among, and also, in the considerable increase of concentration of sebaceous glands in the reticulated layer of derma. In spite of complete loss of hair at an androgenic pelade, germ epithelial elements, being sources of formation of thin (abortive) hairsprings array patterns of which are saved in the skin of hairy part of head, hidden in the layer of sebaceous glands. On the basis of the actual findings in our work revealed, that loss of hairs at an androgenic defluxion filled in due to the physiological hypertrophy of other tissue constituents of skin.